Ergonomic Principles Applied to the Design of the Microsoft Office Computer Keyboard - Hinckley, Ken; McLoone, Hugh (Proceedings of the XVth Triennial Congress of the International Ergonomics Association and the 7th Joint Conference of Ergonomics Society of Korea [and] Japan Ergonomics Society, 2003)
Ergonomic principles of human performance and human-machine interaction are applied to the design of a new, commercially available computer keyboard. Even though it is a primary means to connect people with computer applications, the keyboard has remained relatively static in design. This paper describes concepts and features implemented on a new computer keyboard, addressing negative performance issues as well as promoting new interaction between people and the desktop computer and its software. These concepts were evaluated using methods of design research to positively affect the empathy, efficiency, engagement, and creativity not only for consumption activities but also composition and communication experiences when utilizing the power of computers. The concept of bimanual action was applied to the design of a new left-side pod with a pallet of navigation and editing tools in the non-dominant, left hand. New, dedicated command keys offer one-step, quick action for the most common tasks traditionally performed by reaching and moving mouse or by hidden, awkward keyboard short-cuts.